Xii Simpósio Brasileiro De Gestão E Economia Da Construção 2021
DOI: 10.46421/sibragec.v12i00.408
|View full text |Cite
|
Sign up to set email alerts
|

Barreiras para a gestão de riscos em empresas projetistas

Abstract: Devido à grande quantidade de agentes envolvidos e a diversidade e complexidade das atividades, a gestão de riscos é fundamental para o alcance dos objetivos de empreendimentos da construção civil. Apesar do papel relevante das empresas projetistas nesse processo, sua atuação e nível de profundidade na aplicação de técnicas de gestão de riscos são menores em relação a outros agentes do setor. Este trabalho abordou as barreiras organizacionais e estruturais para a não implementação da gestão de riscos por empre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Probing this analysis, the projects' technical management generally occurs according to a physical-financial schedule. This, in its turn, is elaborated based on information available regarding the estimated cost for materials and labor, deadline, and project design (which determines the construction standard) as stated by Conterato (2018), Roghanian et al (2018), and Regis and Cardoso (2021). As these authors claim, this practice was found to be universally applied by participants in this study.…”
Section: Results Presentation and Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Probing this analysis, the projects' technical management generally occurs according to a physical-financial schedule. This, in its turn, is elaborated based on information available regarding the estimated cost for materials and labor, deadline, and project design (which determines the construction standard) as stated by Conterato (2018), Roghanian et al (2018), and Regis and Cardoso (2021). As these authors claim, this practice was found to be universally applied by participants in this study.…”
Section: Results Presentation and Discussionmentioning
confidence: 85%
“…At CCI, it is common for management deliberations and the administration of small and medium-sized companies to remain centralized in a single person, usually the contractor (also a company's owner or partner) (Magalhães et al, 2018), a habit that results in slowness and incompleteness of processes (Behling & Lenzi, 2019). This leadership profile outcome in general management, specifically for RM, is based on a vicious cycle of subjective analysis focused on an imprecise physical-financial project schedule (Conterato, 2018;Roghanian, Alipour, & Rezaei, 2018;Regis & Cardoso, 2021).…”
Section: Risk Management In CCImentioning
confidence: 99%
See 1 more Smart Citation